2015
DOI: 10.1111/vec.12320
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the in vitro effects of saline, hypertonic hydroxyethyl starch, hypertonic saline, and two forms of hydroxyethyl starch on whole blood coagulation and platelet function in dogs

Abstract: Hypertonic solutions affect platelet function and whole blood coagulation to a greater extent than saline and HES. At clinically relevant dilutions, only CTPFA was markedly more affected by hypertonic solutions than by saline. At high dilutions, HES significantly affects coagulation but to no greater extent than saline at clinically relevant dilutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 49 publications
3
62
2
Order By: Relevance
“…Indeed, a 1:22 dilution of whole blood with 7.2% HTS (mimicking a dose of 4 ml/kg) significantly affected Ct PFA and ROTEM® EXTEM® CFT and MCF in dogs [16]. Moreover, 20% mannitol affected Ct PFA and ROTEM® EXTEM® variables to a greater extent than equimolar 3% HTS in dilutions mimicking recommended clinical doses [17].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a 1:22 dilution of whole blood with 7.2% HTS (mimicking a dose of 4 ml/kg) significantly affected Ct PFA and ROTEM® EXTEM® CFT and MCF in dogs [16]. Moreover, 20% mannitol affected Ct PFA and ROTEM® EXTEM® variables to a greater extent than equimolar 3% HTS in dilutions mimicking recommended clinical doses [17].…”
Section: Discussionmentioning
confidence: 99%
“…Some canine studies have suggested that only hypertonic saline, and not hydroxyl starches (HES) (specifically 130/0.4), result in statistically significant changes to platelet function beyond that associated with haemodilution alone (Wurlod et al . , McBride et al . ).…”
Section: Abnormalities Of Platelet Function Resulting In Haemorrhagementioning
confidence: 99%
“…Two in vitro studies using canine blood reported conflicting conclusions regarding the effect of tetrastarch on platelet function, as measured with a platelet function analyzer . Another recent in vitro study demonstrated impairment in platelet function when canine blood was diluted with both hypertonic hetastarch and hypertonic saline; however, impairment was not noted for dilutions with hetastarch 600/0.75 or hetastarch 130/0.4 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an in vivo study in humans undergoing cholecystectomy and treated with hetastarch 130/0.4 demonstrated reduced MCF that was thought to be related to reduced concentrations of fibrinogen . Animal studies have found similar results regarding impairment of MCF as well as effects on other TEM values such as CT, CFT, and alpha‐angle; however, no in vivo studies in dogs have evaluated resuscitative fluid effects on ROTEM whole blood analysis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation